A Review of Regional Geology of the North Sumatra Basin and Its Paleogene Petroleum System - Ricky A. Tampubolon; Tsania Ozza; M. Tajul Arifin; A. Syauqi Hidayatillah; Aviandito Prasetio; Terry Furqan (Ikatan Ahli Geologi Indonesia, 2017)
The North Sumatra Basin (NSB) is located on the western part of Sundaland and covers approximately 60,000 km2 of onshore and offshore regions. With over 100 years of production, North Sumatra Basin is one of Indonesia’s most prolific sedimentary basins. As stated by Meckel (2012), 25 trillion cubic feet (TCF) of discovered gas reserves (equal to 4.5 billion barrels of oil equivalent, BBOE) and approximately 1.5 BBOE of oil and condensate reserves confirmed this basin as the third largest hydrocarbon-producing basin in Indonesia, after Central Sumatra and Kutei Basins, respectively.The first hydrocarbon discovery was Telaga Said Field in 1885. Since then, remarkable findings (e.g. Rantau, Arun, NSO A, Lhok Sukon A, etc) contributed to the considerable amount of oil and gas reserves. From 1985 onwards, drilling activity in the North Sumatra Basin was stagnant due to volatile geopolitical and geological condition in Aceh. A variety of underexplored plays still remain in the basin, especially from Paleogene and pre-Tertiary age.